Education 3410. Comparative Educational Administration. Program 17 - Parsons, Llewellyn, 1930- (Teacher) (MUN Extension Service, 1979)
Lecture presents an analysis of finance in the 21 integrated school districts of Newfoundland and Labrador. An ETV Production